2005
DOI: 10.1007/s10531-004-7841-4
|View full text |Cite
|
Sign up to set email alerts
|

Flood disturbance and riparian species diversity on the Colorado River Delta

Abstract: Abstract. We investigated the influence of channel migration and expansion on riparian plant species diversity along the lower Colorado River near the United States-Mexico border. Using repeat aerial photography in a GIS we identified and classed areas of low, moderate, and high disturbance frequency caused by channel expansion and migration. Replicate vegetation plots (12 m  12 m) were sampled in each of the three disturbance classes. One-way ANOVA was used to test for differences in species richness, specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 33 publications
2
28
0
Order By: Relevance
“…For example, Cunha et al (1985) mentioned 77 species for the Carajas region, Pará, in the Brazilian Amazonia, and Dsuelmann (1978) registered 91 reptile species in the Ecuadorian Amazonia. This would be explained by the following factors: (1) Riparian ecosystems are between the most diverse, dynamic, and complex biophysical habitats of the world's surface (Tiegs et al 2005). Flood pulses generate a wide spatiotemporal heterogeneity of habitats and resources, which can be used by terrestrial and aquatic species, increasing considerably plant and animal richness in the system (Junk et al 1989).…”
Section: Feeding Strategiesmentioning
confidence: 99%
“…For example, Cunha et al (1985) mentioned 77 species for the Carajas region, Pará, in the Brazilian Amazonia, and Dsuelmann (1978) registered 91 reptile species in the Ecuadorian Amazonia. This would be explained by the following factors: (1) Riparian ecosystems are between the most diverse, dynamic, and complex biophysical habitats of the world's surface (Tiegs et al 2005). Flood pulses generate a wide spatiotemporal heterogeneity of habitats and resources, which can be used by terrestrial and aquatic species, increasing considerably plant and animal richness in the system (Junk et al 1989).…”
Section: Feeding Strategiesmentioning
confidence: 99%
“…Nevertheless, quantifying fluid force is very difficult because the relationship between tree height and water depth changes (Tanaka et al 2006). Many researchers have conducted experiments and/or field investigations on the effects of flooding on floodplain trees (Yamamoto and Kozlowski 1987;Terazawa et al 1992;Terazawa and Kikuzawa 1994;Yamamoto et al 1995;Watanabe et al 1996;Friedman and Auble 1999;Azami et al 2004;Capon 2005;Tiegs et al 2005;Asaeda et al 2009a, b;Tanaka and Yagisawa 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Azami et al (2004) observed that downstream river channels became forested subsequent to dam construction. Changes in floodplain inundation can lead to an increase in floral diversity (Tiegs et al, 2005;Stromberg et al, 2007) or a decrease (Van Oorschot et al, 1998).…”
Section: Introductionmentioning
confidence: 99%